Earnings Management and Firm Value: The Moderating Role of Institutional Ownership - Amrie Firmansyah; Ahmad Reza Azizi; Haniyah Berliana Putri (Center for Risk Management & Sustainability and RSF Press, 2026)
This research aims to examine the effect of earnings management on firm value in the banking subsector in Indonesia, with institutional ownership as a moderating variable. This study uses a quantitative method. Secondary research data comes from financial reports and annual reports of banking subsector companies listed on the main board of the Indonesia Stock Exchange (IDX) from 2019 to 2023. Data were obtained from the website www.idx.co.id and the official websites of banking subsector companies that have gone public. Data collection was carried out during March 2025. Based on purposive sampling, the total research sample was 105 observations. This study shows that there is a relationship between institutional ownership disclosure, earnings management, and firm value. The results of the study indicate that: 1) earnings management has a negative effect on firm value; and 2) the interaction of institutional ownership acts as a moderating variable influencing the negative relationship between earnings management and firm value. The results of this study can contribute to company management, government, and further research.